How does research and development intensity influence the performance of firms through different stages in product life cycle? - Dan Li (Innovation & Management Review, 2025)
Purpose - It is widely acknowledged that the ability of a firm to develop and exploit their innovative capabilities is a critical determinant that maintains their competitive advantage. The purpose is to evaluate the research and development (R&D) inputs and outcomes on the performance of firms in different stages. Design/methodology/approach - Drawing on a sample of 30 firms over 8 years (2009-2016), the results from a three-stage Bayesian stochastic frontier analysis model support were used. Findings - Some interesting findings were discovered. First, the R&D intensity is positively associated with the number of patents granted, which is negatively associated with the number of new drug approvals (NDAs). Second, R&D inputs, including expenditures and human resources, are negatively related to the number of NDAs and firm performance. Third, state-owned firms perform better and have more patents granted than private-owned firms in China. Finally, the traditional Chinese medicine firms and non-coastal firms both gain fewer profits, but they generate more new drugs than chemical drug firms and coastal firms in terms of policy support. Originality/value - It is revealed that there are no common factors among Chinese pharmaceutical firms except for ownership, and this heterogeneous behavior indicates that there is no common factor for enhancing the efficiency of all Chinese pharmaceutical firms.
Keywords: 650; Innovation; Bayesian stochastic frontier analysis; Performance; Efficiency